Monitorowanie zachowań osób skazanych za przestępstwa na tle seksualnym - Herbowski, Piotr; Słapczyńska, Dominika (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
In Poland there is a lack of effective solutions to monitor people convicted of sexual offenses. Operational activities also have a limited effectiveness. Therefore, it is advisable to conduct periodic polygraph examinations of the most dangerous perpetrators of such crimes. These examinations should be considered as a special protection measure, similar to the register of sex offenders.
Keywords: sex offenders; operational activities; polygraph examination